When Crickets Cry : a novel of the heart - Martin, Charles, 1969- (Nashville, TN : WestBow Press, 2005)
"It begins on the shaded town square in a sleepy Southern town. A spirited seven-year-old has a brisk business at her lemonade stand. Her latest customer, a bearded stranger, drains his cup and heads for his car, his mind on a boat he's restoring at a nearby lake. But the little girl's pretty yellow dress can't hide the ugly scar on her chest. The stranger understands more about it than he wants to admit. And the beat-up bread truck careening around the corner with its radio blaring is about to change the trajectory of both of their lives."--COVER.
A Southern Living book of the month selection.
new book 2022 winter.
Accelerated Reader AR
Keywords: Physicians -- Fiction; Heart -- Transplantation -- Fiction; Transplantation; Georgia -- Fiction; Fiction; Christian fiction